Sri Lankan natural graphite/gel polymer electrolyte based electrochemical double layer capacitor - D. S. K. Rajaguru; K. P. Vidanapathirana; K. S. Perera (Ceylon Journal of Science, 2021)
Supercapacitors are a promising elucidation among the energy storage devices to cater to the ever-increasing energy demand. Graphite takes a prominent place as a carbonaceous electrode material in electrochemical double layer capacitors (EDLCs) to fulfill the requirement. The present study is based on the performance evaluation of an EDLC fabricated with Sri Lankan natural graphite electrodes incorporating a gel polymer electrolyte. Electrochemical properties of the laboratory scale device were examined using cyclic voltammetry (CV) and galvanostatic charge discharge (GCD) techniques. EDLC displayed a single electrode specific capacitance (Csc) of 5.33 F g-1 with CV which retained 84.8% capacity from its initial value after 500 cycles. GCD results revealed initial single electrode discharge capacitance (Csd) of 0.69 F g-1 with 91.3% retention from its initial value after 10,000 charging and discharging cycles.